RA01.08: LAPAROSCOPIC ROUX-EN-Y GASTROJEJUNOSTOMY FOR GASTRIC CONDUIT OUTLET OBSTRUCTION FOLLOWING ESOPHAGECTOMY FOR CANCER. (14th September 2018) - Bernardi, Daniele; Porta, Matteo; Asti, Emanuele; Lazzari, Veronica; Ceriani, Chiara; Bonavina, Luigi
Abstract: Description: After Ivor Lewis esophagectomy, gastric outlet obstruction refractory to prokinetic therapy and/or endoscopic pyloric dilatation is a challenging clinical problem. Thoracoscopic implant of a gastric neurostimulator has been reported to be effective, but long-term results are lacking. The patient, a 57-year-old woman, underwent a Ivor Lewis esophagectomy for T1N0 adenocarcinoma in 2007. Postoperatively, the patient complained of persistent dysphagia, regurgitation, and 29-kg weight loss. A mechanical obstruction was ruled out by barium swallow study and upper gastrointestinal endoscopy. Several conservative attempts with prokinetic agents and endoscopic dilatations failed, and the patient was exclusively fed through jejunostomy until the thoracoscopic implant of a gastric neurostimulator in October 2015. The postoperative course was uneventful. At six-months follow-up, the patient was able to assume a soft diet and reported a weight gain of 3 kg, with a significant improvement of the total symptom score and gastric emptying scintigraphy. Nevertheless, this encouraging clinical benefit gradually disappeared after the first year of follow-up. At the beginning of 2017, the patient experienced persistent episodes of vomiting and returned to jejunostomy feeding. The video shows the technique of laparoscopic Roux-en-Y gastrojejunostomy. After adhesiolysis and transhiatal mobilization of the distal gastric conduit, a 50 cm long Roux-en-Y alimentary limb was fashioned and anastomosed to the antrum. Post-operative course was uneventful and a gastrographin swallow study showed a satisfactory emptying of the conduit. At the 3-month follow-up the patient was able to resume a soft oral diet. Laparoscopic Roux-en-Y gastrojejunostomy appears to be safe and effective in treating refractory gastric outlet obstruction following Ivor-Lewis esophagectomy. Disclosure: All authors have declared no conflicts of interest.